The incidence of malignant melanoma in two different cultural settings and the probable role of clothing in melanoma prevention - Leila Dehghani; Narges Khanjani; Abbas Bahrampoor (Shahid Sadoughi University of Medical Sciences, 2014)
Introduction: Malignant melanoma is a fatal cutaneous neoplasm and one of the fastest growing cancers worldwide. The objective of this study is to evaluate the prevalence of melanoma in different cultural settings and the probable role of clothing for prevention. Materials and Methods: In this cross-sectional study, data about diagnosed melanoma patients in Kerman Province, Iran including age, pathology, sex, location, and site of skin involvement, were obtained from the Kerman and Rafsanjan Cancer Registries from 2005 to 2009. Similar data related to melanoma incidence in Victoria, Australia were obtained from the Victorian Cancer Council, Melbourne. Incidence by age, sex and site of skin was calculated in both Kerman Province and Victoria State. Then the incidence differences for exposed and unexposed limbs were calculated and compared. Results: Melanoma incidence in Kerman was 5.7 in million annually. Incidence in men was higher than women. The highest incidence was seen in 70-79 years of age. Most cases of melanoma (30%) were localized in the face. Incidence in Victoria State was 431.9 in million annually. The incidence in men was more than women. The highest incidence was seen above 80 years of age. Most of the cases (30.1%) of melanoma were seen in the trunk and then arm with 22.1%. The incidence difference between the two nations was significant except for the hands and male's feet. Conclusion: The present study suggests that clothing is possibly preventing about 25.7, 37.4 and 72.6 cases of melanoma respectively in the trunk, arm and leg in 1,000,000 people annually in Iran.